The biomechanics of the vagina: a complete review of incomplete data - Justin Dubik; Marianna Alperin; Raffaella De Vita (npj Women's Health)
Abstract The biomechanical properties of the vagina are crucial to fulfilling physiological functions such as menstruation, sexual intercourse, pregnancy, and childbirth. Alterations to these properties are associated with pathological conditions that profoundly affect women. This review provides a comprehensive synthesis of the limited and inconsistent data on the biomechanics al properties of the vagina as they relate to pregnancy, parity, prolapse, and menopause, guiding new research efforts that advance women’s health.